Impact Of Service Quality and Location on Customer Satisfaction - Zuhron, Aziz Miftahuz; Wijaya, Rahmad; Fiandari, Yulist Rima (Universitas Muhammadiyah Malang, 2024)
This research aims to understand the impact of service quality and location on customer satisfaction. This study uses data analysis, i.e., double linear regression analysis. The results of this study are that the quality of service has a partial and significant impact on customer satisfaction and the location has a Partial and Significant impact on customer satisfaction. Quality of service and location simultaneously affect customer satisfaction. The recommendation for this research is the quality of service in PT. TIKI is improved so that customers are satisfied. And a more strategic location so that customers are satisfied with PT. TIKI.